Single- vs. multiple-set resistance training: Recent developments in the controversy - Galvao, D. A.; Taaffe, D. R. (The Journal of Strength and Conditioning Research, 2004)
The number of sets in a resistance training program is a major point of discussion and controversy. The purpose of this paper is to present an overview of recent resistance training studies comparing single and multiple sets.